Crop diversification for a sustainable agriculture - Rautaray, S K; Sucharita, Swati (Indian Farming, 2024)
Crop diversification is a component of conservation agriculture. It is useful in enhancing plant productivity, quality, health and nutritional value and/or building crop resilience to biotic and abiotic stresses. It reduces the risk of huge crop loss and provides ecosystem services such as pollination, carbon sequestration, nutrient cycling and biodiversity promotion. At regional scale, the objective of the Government is to reduce the regional dominance of one crop to regional production of a number of crops. However, the importance of crop diversification is often overlooked due to profit motive from crops such as rice, wheat and sugarcane having assured market with the provision of minimum support price. Considering the importance of crop diversification, several Government programmes are under implementation. Ways for popularizing crop diversification is outlined in this article.